A Review of Non-1H RF Receive Arrays in Magnetic Resonance Imaging and Spectroscopy - Matthew Wilcox; Steven M. Wright; Mary McDougall (IEEE Open Journal of Engineering in Medicine and Biology)
It is now common practice to use radiofrequency (RF) coils to increase the signal-to-noise ratio (SNR) in 1H magnetic resonance imaging and spectroscopy experiments. Use of array coils for non-1H experiments, however, has been historically more limited despite the fact that these nuclei suffer inherently lower sensitivity and could benefit greatly from an increased SNR. Recent advancements in receiver technology and increased support from scanner manufacturers have now opened greater options for the use of array coils for non-1H magnetic resonance experiments. This paper reviews the research in adopting array coil technology with an emphasis on studies of the most commonly studied non-1H nuclei including 31P, 13C, 23Na, and 19F. These nuclei offer complementary information to 1H imaging and spectroscopy and have proven themselves important in the study of numerous disease processes. While recent work with non-1H array coils has shown promising results, the technology is not yet widely utilized and should see substantial developments in the coming years.